Technology and public management - Shark, Alan R. (New York, NY : Routledge, 2023)
"Students of public administration, public policy, and nonprofit management require a strong foundation in how government and NGOs are connected with information technology. Whether simplifying internal operations, delivering public-facing services, governing public utilities, or conducting elections, public administrators must understand these technological tools and systems to ensure they remain effective, efficient, and equitable. This innovative textbook is designed for students of public affairs at every level who need to know and understand how technology can be applied in today's public management workplace. The book explores the latest trends in technology, providing real-life examples about the need for policies and procedures to safeguard technology infrastructure while providing greater openness, participation, and transparency. In Technology and Public Management, Second Edition, author Alan Shark informs, engages, and directs students to consider best practices, with new material on emerging tech, data management and analytics, artificial intelligence, and cybersecurity. This thoroughly updated second edition explores: A broad range of technologies that government, nonprofit partners, and citizens depend upon to deliver important infrastructure, including security, education, public health and personal healthcare, transit and transportation, culture and commerce, to name a few. Growing mistrust in government, and the role technology can play in ameliorating it. Emerging and adapted technologies to help government achieve ambitious goals, including drawing carbon out of the atmosphere, empowering students everywhere to learn effectively at home or at school, improving healthcare, providing affordable housing, enabling agriculture to keep pace with population growth, and improving scores of other public services. The critical insights and management skills needed to argue for investments in information technology as necessary priorities for our public organizations to improve public services and resources. Reader-friendly and jargon-free, this textbook is required reading for students enrolled in public administration and nonprofit management programs, as well as for practicing public administrators looking for a better understanding of how technology may be successfully and responsibly used in public organizations. It is equally valuable as a text for MBA, social work, education, public health, and other degree programs that produce graduates who will work with and within those organizations that deliver public services, broadly defined"--
Contemporary trends in public administration and technology -- Governance and leading innovation : who decides? -- E-government and digital government: the rise of the new civic media -- Broadband, mobility, and the internet : policies and technology -- The data factor : transparency, reform, and improved data-driven decisions -- Managing knowledge and data management -- Geospatial systems and planning : mapping and visualizing the future -- Managed software, hardware, and shared services : once upon a cloud -- Assessing and measuring it performance -- Cybersecurity : understanding and managing risk -- The people factor : managing the human resource function in a technology environment -- Ethics and digital equity -- Nonprofit technology management -- Future challenges : artificial intelligence, robotics, privacy, public trust.
OCLC-licensed vendor bibliographic record.
Keywords: Public administration -- Technological innovations; Internet in public administration; Electronic government information; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General